Ion Beam Assisted E-Beam Deposited TiN Microelectrodes—Applied to Neuronal Cell Culture Medium Evaluation - Ryynänen, Tomi; Toivanen, Maria; Salminen, Turkka; Ylä-Outinen, Laura; Narkilahti, Susanna; Lekkala, Jukka (Frontiers in Neuroscience, 2018)
Microelectrode material and cell culture medium have significant roles in the signal-to-noise ratio and cell well-being in in vitro electrophysiological studies. Here, we report an ion beam assisted e-beam deposition (IBAD) based process as an alternative titanium nitride (TiN) deposition method for sputtering in the fabrication of state-of-the-art TiN microelectrode arrays (MEAs). The effects of evaporation and nitrogen flow rates were evaluated while developing the IBAD TiN deposition process. Moreover, the produced IBAD TiN microelectrodes were characterized by impedance, charge transfer capacity (CTC) and noise measurements for electrical properties, AFM and SEM for topological imaging, and EDS for material composition. The impedance (at 1 kHz) of brand new 30 µm IBAD TiN microelectrodes was found to be double but still below 100 kΩ compared with commercial reference MEAs with sputtered TiN microelectrodes of the same size. On the contrary, the noise level of IBAD TiN MEAs was lower compared with that of commercial sputtered TiN MEAs in equal conditions. In CTC of IBAD TiN electrodes (3.3 mC/cm2) also outperformed the sputtered counterparts (2.0 mC/cm2)was 3.3 mC/cm2.. To verify the suitability of IBAD TiN microelectrodes for cell measurements, human pluripotent stem cell (hPSC)-derived neuronal networks were cultured on IBAD TiN MEAs and commercial sputtered TiN MEAs in two different media: neural differentiation medium (NDM) and BrainPhys (BPH). The effect of cell culture media to hPSC derived neuronal networks was evaluated to gain more stable and more active networks. Higher spontaneous activity levels were measured from the neuronal networks cultured in BPH compared with those in NDM in both MEA types. However, BPH caused more problems in cell survival in long-term cultures by inducing neuronal network retraction and clump formation after 1-2 weeks. In addition, BPH was found to corrode the Si3N4 insulator layer more than NDM medium. The developed IBAD TiN process gives MEA manufacturers more choices to choose which method to use to deposit TiN electrodes and the medium evaluation results remind that not only electrode material but also insulator layer and cell culturing medium have crucial role in successful long term MEA measurements.